2018
DOI: 10.4103/ijem.ijem_438_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of osteoporosis in apparently healthy adults above 40 years of age in Pune City, India

Abstract: Purpose:The aim of study was to assess the prevalence of osteoporosis and changes in bone mass with increasing age and compare bone health status of apparently healthy men, premenopausal and postmenopausal women.Methods:Data were collected on anthropometric and sociodemographic factors in 421 apparently healthy Indian adults (women = 228), 40–75 years of age, in a cross-sectional study in Pune city, India. Bone mineral density (BMD) was measured by dual-energy X-ray absorptiometry at two sites-lumbar spine (LS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 26 publications
0
19
1
Order By: Relevance
“…We noticed that the means of BMD T -scores in the regions of interest in our study were worse than those in previous studies [4648], probably because all our subjects are diagnosed with type 2 diabetes, and DM, as demonstrated in previous studies, is a contributing factor to such difference because of its effect at the cellular level. Prolonged hyperglycemia is found to affect both the function and quantity of osteoblasts by disrupting the response to vitamin D and stimulating glycation of multiple proteins.…”
Section: Discussioncontrasting
confidence: 87%
“…We noticed that the means of BMD T -scores in the regions of interest in our study were worse than those in previous studies [4648], probably because all our subjects are diagnosed with type 2 diabetes, and DM, as demonstrated in previous studies, is a contributing factor to such difference because of its effect at the cellular level. Prolonged hyperglycemia is found to affect both the function and quantity of osteoblasts by disrupting the response to vitamin D and stimulating glycation of multiple proteins.…”
Section: Discussioncontrasting
confidence: 87%
“…In men, a small longitudinal bone loss is observed throughout life, whereas in women there is an additional bone loss in association with estrogen insufficiency during peri-menopausal and post-menopausal period. 13 A study carried out by Hernlund E, et al found out 21% of females and 6% of males residing in Sweden to be osteoporotic. This study showed 3-4 times more osteoporosis in the female population than in the male.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis causes the bones to be fragile and increases susceptibility to fracture even with trivial trauma. [1] After attainment of menopause in women, the process of osteoporosis is accelerated by estrogen deficiency. Estrogen helps in maintaining a positive calcium balance and in osteogenesis.…”
Section: Introductionmentioning
confidence: 99%